Lives in transit in early modern England : identity and belonging - Das, Nandini, 1974- (Connected histories in the early modern world., 2022)
What did it mean in practice to be a 'go-between' in the early modern world? How were such figures perceived in sixteenth and seventeenth century England? And what effect did their movement between languages, countries, religions and social spaces - whether enforced or voluntary - have on the ways in which people navigated questions of identity and belonging? 'Lives in Transit in Early Modern England' is a work of interdisciplinary scholarship which examines how questions of mobility and transculturality were negotiated in practice in the early modern world. Its twenty-four case studies cover a wide range of figures from different walks of life and corners of the globe, ranging from ambassadors to Amazons, monarchs to missionaries, translators to theologians. Together, the essays in this volume provide an invaluable resource for people interested in questions of race, belonging, and human identity.